2020
DOI: 10.22270/ajprd.v8i3.746
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Evaluation Of Different Brands Of Metformin Hydrochloride Film Coated Tablets Marketed In Addis Ababa, Ethiopia

Abstract: Metformin hydrochloride is a biguanide class of drug widely used to treat Type 2 diabetes mellitus. Its oral bioavailability is about 50 to 60 % with a half-life of about 3 h. This study focused on evaluation and comparison of the physicochemical properties of different brands of metformin hydrochloride (500mg) film coated tablets available in drug retail outlets in Addis Ababa, Ethiopia. Some different in vitro tests including hardness, weight variation, disintegration time, dissolution study, and assay were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(18 reference statements)
2
0
0
Order By: Relevance
“…Our findings showed that the variation of tablets' thickness was within the accepted limit; ±5%, where it was ranged between±0.01 and 0.10%. In agreement with our findings, a previous study revealed the closeness of all filmcoated tablets' thickness, where the standard deviation was found between 0.02-0.06 [22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings showed that the variation of tablets' thickness was within the accepted limit; ±5%, where it was ranged between±0.01 and 0.10%. In agreement with our findings, a previous study revealed the closeness of all filmcoated tablets' thickness, where the standard deviation was found between 0.02-0.06 [22].…”
Section: Discussionsupporting
confidence: 93%
“…As a result, the high value in hardness making the products able to withstand mechanical shocks during manufacturing, handling, packaging, and transportation processes. This finding was in line with a previous study conducted on metformin tablets, which concluded that the crushing strength of the products was above the satisfactory limit; however, they showed no impact on disintegration [22]. Another review article emphasized that if the tablet's hardness is too high, it is essential firstly to check its disintegration before rejection.…”
Section: Discussionsupporting
confidence: 88%